AB0797 A randomised double blind placebo controlled trial to compare the efficacy of initial combination therapy vs monotherapy for pulmonary arterial hypertension in systemic sclerosis. (12th June 2018) - Dwivedi, P.; Sharma, S.K.; Dhir, V.; Rohit, M.K.; Behera, D.; Jain, S.
Abstract : Background: Pulmonary Arterial Hypertension(PAH) is one of the leading cause of death in Systemic Sclerosis(SSc) population. Trials that have studied the efficacy of initial oral combination therapy versus monotherapy for the treatment of PAH in SSc are limited. Objectives: To study the efficacy and safety of monotherapy (sildenafil) versus initial combination therapy (sildenafil and bosentan) for treatment of SSc related PAH. Methods: In a single centre, double blind, prospective, randomised, placebo controlled trial, 34 patients of SSc related PAH defined as Pulmonary Artery Systolic PressuresPASP>35 mmHg as measured by echocardiography, New York heart Association(NYHA) functional class II and III with forced vital capacity >60% were randomised in 1:1 ratio to sildenafil (20 mg thrice a day) and matched placebo of bosentan to one study arm or to the combination of sildenafil(20 mg thrice a day) and bosentan (62.5 mg twice daily for 4 weeks maximum up to 125 mg twice daily) to the other arm for 24 weeks. The primary end point of the study was to assess the change in pulmonary artery pressures measured by echocardiography at 24 weeks from baseline. The secondary efficacy end points was to compare the change in 6 min Walk Distance (6MWD), Time To Clinical Worsening(TTCW) and adverse events at 24 weeks. Intention to treat analysis was carried for the primary and secondary outcomes. p<0.05 was considered significant. Kaplan Meier survival analysis was done to estimate the time to PAH worsening and hazard ratio was calculated. Results: The mean change in Pulmonary Artery Systolic Pressures in the monotherapy arm was −1.0 mmHg versus +2.1 mmHg in the combination arm (p=0.56). TTCW is prolonged in the combination arm. The mean survival time in the initial combination arm was 23.76±0.59 weeks and 23.28±0.23 weeks in the monotherapy arm. The hazard ratio was 0.73{95% C.I 0.04–11.7} (p=0.87). The mean change in the 6 min walk distance in the monotherapy arm was 15.88±31.83 m and 25.88±38.25 m in the combination arm (p=0.38). The satisfactory clinical response in the combination arm was 82.3% versus 70% in the monotherapy arm (O.R=1.9C.I 0.38–9.88 p=0.44). The upfront combination of sildenafil and bosentan was well tolerated with similar rates of adverse events in both group. Conclusions: In this study we could not demonstrate any significant difference in the efficacy of initial combination therapy of sildenafil and bosentan over sildenafil monotherapy. The patients of systemic sclerosis tolerated the initial combination of sildenafil and bosentan well and the treatment prevented further deterioration. Larger studies with more number of subjects may be required to confirm the results. Trial Registration- Clinical Trials.gov:NCT03053739 Disclosure of Interest: None declared